COMPARISON BETWEEN CONDITION-BASED, AGE-BASED AND FAILURE-BASED MAINTENANCE POLICIES IN PARALLEL AND SERIAL CONFIGURATIONS: A SIMULATION ANALYSIS - Azadeh, Ali; Sheikhalishahi, Mohammad; Abdolhossein Zadeh, Saeed; Heidaryan Baygy, Hossein (International Journal of Industrial Engineering: Theory, Applications and Practice, 2017)
This paper evaluates the performance of condition-based maintenance (CBM), age-based maintenance (ABM) and failure-based maintenance (FBM) policies in serial and parallel multi-resource systems. CBM is mainly taken into account as a significant maintenance policy that makes use of the operating circumstances of the component to predict a failure occurrence, so that the component is preventively maintained only when necessary. ABM and FBM are considered as two alternatives for CBM. In this paper, these three techniques are compared with each other using simulation. To evaluate and analyze these three policies in parallel and serial configurations, three performance indicators comprising efficiency, total maintenance cost and average queue length are introduced for all scenarios. An explanatory case study is used to investigate the performance of these policies in various circumstances. The results demonstrate that in general, CBM outperforms ABM, and on the other hand, ABM shows better results in comparison to FBM.